Nicorandil Elevates Tissue cGMP Levels in a Nitric-Oxide-Independent Manner - Yukiko Minamiyama; Shigekazu Takemura; Seikan Hai; Shigefumi Suehiro; Shigeru Okada; Yoshihiko Funae (Elsevier, 2007)
The K+ channel opener nicorandil is a hybrid compound that contains nitrate in its structure. It has been reported that nicorandil can relax vascular tissue in vitro via a mechanism that involves activation of KATP channels and stimulation of soluble guanylyl cyclase. However, it is not known whether the increase of cGMP levels occurs through an elevation of nitric oxide (NO). The aim of the present study was to determine whether NO release was a direct effect of nicorandil. We reported here that nicorandil did not generate NO using ozone chemiluminescence detection methods in human or rat liver microsomes (P450-rich fractions) with addition of NADPH. However, nicorandil elevated cGMP levels in rat liver, aorta, and human coronary smooth muscle cells in vitro. The elevation was not inhibited by the NO trapping agent carboxy-2-phenyl-4,4,5,5-tetramethyl-imidazoline-1-oxyl-3-oxide (carboxy-PTIO). These results suggest that nicorandil elevates cGMP without NO generation. Keywords:: nicorandil, nitric oxide (NO), cGMP, P450